A Study On Process-Generated Crystal Defects And Corresponding Leakage Current Of P-N Junctions In Bipolar Transistors - Cheah , Chun Yee (2010)

(untitled)
An investigation into excess reverse leakage current of p-n junction process control structures in an industrial bipolar junction transistor technology is detailed in this work. Excess leakage is shown to be caused by rod-like crystal defects generated from a boron implantation process. The rod-like defects are suggested to consist of selfinterstitials in the silicon lattice. The defects were reduced by optimizing the scattering oxide growth prior to implantation. Phenomenological models are then proposed to explain how self-interstitials were reduced by process optimization. Oxidation was performed in dry ambient and above the viscous flow temperature to relieve the interfacial stress during oxide growth. It is suggested that by doing so, interstitial injection into silicon is eliminated.